OPTIMIZATION OF TECHNOLOGICAL PROPERTY OF RICE HUSK ASH (RHA) - Kimpa, Mohammed Isah; Durumin-Iya, Sani Garba; Sadiq, Yusuf Abubakar; Abubakar, 1Ahmad Alhaji; Uzair, Muhammad; Zakar, 2Muhammad Nasiru; Isah, 1Kasim Uthman (FUDMA Journal of Sciences, 2024)
Recently, rice husk (RH) has attracted researchers attention for their possibilities to be more than any other crop remnant, this is due to its availability and promising nature. Averagely, 500 million tonnes of rice are produced worldwide each year, leaving behind huge amounts of waste that will be used in our cement and ceramic industries to produce 100 million tonnes of husk as a variety of byproducts.. When rice husk is incinerated, it produced a high quantity of ash known as Rice Husk Ash (RHA). On average, 200 kg complete combustion of rice husk ash is obtained from one tonnes of rice husk. Raw Paddy Rice was bought and blended with motar to extract rice husk. The grinded paddy was extracted locally by spreading the rice on tray and blew into air in an enclosed room. The RH was calcinated at 700°C for 1hour 30mins, grind and sieve to remove agglomeration. The sample was treated with NaOH and HCl acid to remove the unwanted material and enhance the silica production. X-ray fluorescence and X-ray Diffraction analysis results revealed RHA treated with NaOH is rich in silica with about 19.33 (4%wt) molecular structure, which indicated that chemical treatment play a vital role in improving the physico-chemical properties of RHA.
Keywords: Rice husk; Rice husk ash; Silica production